Analisis Efektifitas Pasal 385 KUHP (Lama) Dalam Penanggulangan Penyelesaian Perkara Penyerobotan Tanah Yang Terjadi Di Indonesia - Datau, Frieska Jayanthi; Puluhulawan, Fenty U.; Mantali, Avelia Rahma Y. (CV. ITTC INDONESIA, 2023)
The act of illegal land grabbing is an unlawful act, which can be classified as a criminal act. The purpose of this study was to analyze the effectiveness of Article 385 of the (old) Criminal Code in overcoming the settlement of land grabbing cases that occurred in Indonesia. The type of research that the writer did was to do research on normative juridical research. Land grabbing is an act that indicates a crime and is against the law because it is done by grabbing an object, in this case land that is already owned by another person with the intention of being controlled without rights. Criminal penalties in the form of a maximum of four years in prison can be imposed on a person who commits fraud by taking over someone else's land.